2010
DOI: 10.1213/ane.0b013e3181c293bd
|View full text |Cite
|
Sign up to set email alerts
|

Single-Injection Percutaneous Peribulbar Anesthesia with a Short Needle as an Alternative to the Double-Injection Technique for Cataract Extraction

Abstract: The single-injection technique for percutaneous peribulbar anesthesia with a short needle is a suitable alternative to the double-injection technique for cataract surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 8 publications
0
13
0
1
Order By: Relevance
“…Classically, PBA involves two injections, one ventrolateral (VL; named inferotemporal in the human literature), and the second dorsomedial (DM; named superonasal in the human literature); however studies in humans have shown that the distribution of the local anesthetic is similar with one injection site or two, and one injection may be safer (Demirok et al. ; El Said & Kabeel ; Ghali & Hafez ; Nouvellon et al. ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Classically, PBA involves two injections, one ventrolateral (VL; named inferotemporal in the human literature), and the second dorsomedial (DM; named superonasal in the human literature); however studies in humans have shown that the distribution of the local anesthetic is similar with one injection site or two, and one injection may be safer (Demirok et al. ; El Said & Kabeel ; Ghali & Hafez ; Nouvellon et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…The injection of a large volume (6-12 mL in humans) encourages anterior spread to the eyelids, providing more complete analgesia as well as akinesia of the orbicularis oculi muscle (Ripart et al 2001;Nouvellon et al 2010a,b). Classically, PBA involves two injections, one ventrolateral (VL; named inferotemporal in the human literature), and the second dorsomedial (DM; named superona-sal in the human literature); however studies in humans have shown that the distribution of the local anesthetic is similar with one injection site or two, and one injection may be safer (Demirok et al 1997;El Said & Kabeel 2010;Ghali & Hafez 2010;Nouvellon et al 2010b). Recently, the PBA technique has been reported in dogs for eyelid surgery and (in combination with RBA) for enucleations; however the method described involves a four-site injection technique (dorsally, ventrally, laterally and medially) (Giuliano 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Con la misma técnica anestésica aplicada a 857 pacientes, se encontró que después de los 7 min el 100% de los pacientes tenía un bloqueo adecuado para cirugía 7 . Otros autores han documentado que un bloqueo efectivo se inicia después de 10 min con esta técnica 8 .…”
Section: Discussionunclassified
“…The authors[11] proved in a previous study that the single-injection technique for percutaneous PBA with a short needle as described by Rizzo et al . [10] provided adequate akinesia and analgesia for cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…It requires a single puncture rather than multiple punctures and provides adequate analgesia and akinesia. [11]…”
Section: Introductionmentioning
confidence: 99%